Pengaruh Tekanan Stakeholder, Ukuran Perusahaan, dan Kepemilikan Institusional Terhadap Publikasi Sustainability Report - Rino Wahyudi; Dirvi Surya Abbas; Reni Anggraeni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this study is to determine the effect of the audit committee, stakeholder pressure, company size, institutional ownership on the publication of the sustainability report. In Manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 Period. This study uses a quantitative approach. The population in this study were 195 manufacturing companies listed on the IDX. The sampling technique used is purposive sampling. Based on the predetermined criteria, 11 samples of manufacturing companies were obtained. The type of data used in this research is secondary data. The method used is panel data regression analysis. The results of this study indicate that simultaneously Shareholder Pressure, Company Size, Institutional Ownership simultaneously affect the Sustainability Report Publication. Partially, the size of the company has a positive effect on the publication of the sustainability report. while the audit committee, shareholder pressure, institutional ownership have no effect on the publication of the sustainability report.